API and PNR data in use for border control authorities. Issue 4 (October 2017) - Han, Chang-Ryung; McGauran, Rachel; Nelen, Hans
Abstract Airplanes transport a large number of travelers simultaneously, and airports are often described as inland borders where strangers converge and disperse. They are also a conduit for terrorism and transnational crimes. Border control authorities have endeavored to obtain information regarding travelers' identification, baggage and travel intentions in advance in order to detect and deter terrorism and transnational crime in an efficient manner. However, the transmission of detailed personal information – an integral feature of advance passenger information (API) and passenger name record (PNR) data – gives rise to concerns about privacy and data protection. This article contests that API and PNR data ought to be examined within the context of the broad array of risk management activities undertaken by border control authorities. The collection of such data for border control can also lead to better-informed decisions and judgement calls by investigators regarding which travelers to apprehend, as distinct from the current, seemingly arbitrary and often intuition-based decisions, and the consequent intrusion of privacy that such investigations entail.